Analysis of HSS Chisel Hardness on a Lathe Machine Through Heat Quenching Treatment at the Production Workshop of the Department of Mechanical Engineering, Bengkalis State Polytechnic - Razali, Razali; Syahrizal, Syahrizal; Rianto, Arauf (ABEC Indonesia, 2024)
Based on the results of the Field Study at the Bengkalis State Polytechnic Machine Tool Workshop practice, duringthe metal cutting machining process, there is an interaction between the tool and the workpiece. The friction experienced bythe tool is caused by the flowing grunt surface and the surface of the workpiece that has been cut. As a result of this friction,the tool suffers from wear. The wear of this tool will increase to a certain extent. The length of time it takes to reach this wearlimit is defined as tool life. The factors that affect tool wear are temperature and cooling media on the average value of aresponse. From the data, it can be seen that the decrease in wear from temperature from 800 to 1000 0C there is a significantdecrease in the average response. For the refrigerant media factor, the difference in influence between salt, bromus oil, andSAE 20 oil was also seen, where salt provided the highest average HSS tool wear value, followed by bromus oil, and the lowest wear was SAE 20 oil of 0.066 mm. This indicates that the tool wear is lower and the tool is harder than the tool before heattreatment quanching at 1000 °C